The Effect of Individual and Environmental Motivations on YouTuber Followers' Behavioral Changes - F. Gorgun Deveci; Sevtap Unal (Istanbul Business Research (IBR), 2021)
This study aimed to determine the effective factors on the behavioral changes of YouTuber followers. Accordingly, it was targeted to determine the effect of the individual, environmental motivations, and YouTuber characteristics on the change of followers' behavior through the online flow process. Meanwhile, the mediating role of opinion seeking and the moderator role of the fear of missing out have been discussed. The main mass consisted of 520 female consumers who live in Istanbul, are at least 18 years of age, and follow at least one YouTuber in the makeup/cosmetic/beauty segment. Structural equation modelling was used to analyze the data. Findings showed that three subdimensions of knowledge-sharing motivations, which are consumer interactivity, trust, and consumer expertise; four subdimensions of fundamental interpersonal relation orientations, which are the need to be part of a group, avoidance of similarity and unpopular choice counter-conformity, creative choice counter-conformity, and the need for personal growth; and social presence have a positive, community identification and that YouTuber characteristics have a negative effect on online flow. However, social norms have no effect. Meanwhile, online flow is effective on the behavioral changes of followers. Finally, opinion seeking has a mediating role whereas the fear of missing out has a moderating role.
Keywords: 650; Individual Motivations; Environmental Motivations; YouTuber Characteristics; Online Flow Theory; Behavioral Changes